The negative impact of cadmium on nitrogen transformation processes in a paddy soil is greater under non-flooding than flooding conditions. (August 2019) - Afzal, Muhammad; Yu, Mengjie; Tang, Caixian; Zhang, Lujun; Muhammad, Niaz; Zhao, Haochun; Feng, Jiayin; Yu, Lu; Xu, Jianming
Abstract: Nitrification and denitrification are two important processes in the nitrogen (N) cycle. Under heavy-metal pollution with water management of paddy soils, these two processes are not well understood. This study aimed to examine the effect of cadmium (Cd) on N transformation under flooding and non-flooding conditions. A paddy soil was incubated under two water regimes (flooding and non-flooding) and four Cd levels (0, 2, 5 and 10 mg kg −1 ). The availability of Cd was higher in the non-flooding than flooding conditions. Cadmium contamination significantly ( p  ≤ 0.05) decreased the copy number of archaeal and bacterial amoA genes, bacterial nirS, nirK and nosZ genes under both conditions with the decrease being greater under non-flooding. High level of Cd (10 mg kg −1 ) was more toxic in non-flooding than flooding conditions to the nitrifiers and denitrifiers, which in turn decreased N transformation through microbially-mediated processes. Its contamination decreased N2 O emission initially under both water regimes but the effect was greater under the non-flooding condition. However, the non-significant stimulatory effect of Cd on N2 O emission was observed during the late phase. The microbial community structure was changed with time and water regimes. Irrespective of water regime, the dominated fungal phyla were Ascomycota and Basidiomycota while the dominated bacteria phyla were Actinobacteria, Proteobacteria, Firmicutes and Acidobacteria . In summary, water regimes and Cd bioavailability changed soil N transformations via microbial mediated processes. Graphical abstract: Unlabelled Image Highlights: Cadmium decreased the abundance of nitrifiers and denitrifiers in the paddy soil. Cd contamination decreased N2 O emission initially under both water regimes. The dominated fungal phyla were Ascomycota and Basidiomycota. Bacterial but not fungal community composition changed by water management practices. N transformation decreased in Cd polluted soil more in non-flooding than flooding.